2022
DOI: 10.1590/0103-6440202204222
|View full text |Cite
|
Sign up to set email alerts
|

The metal post material influences the performance of artefact reduction algorithms in CBCT images

Abstract: This study aimed to assess the effect of the MAR tool on the expression of artefacts in different regions of a tooth restored with different types of metal posts. Alveolar sockets (anterior, and posterior region) of a mandible and an unirradicular tooth were used. Cone beam computed tomography scans of the tooth without a metal post, and with cobalt-chromium (Co-Cr), nickel-chromium (Ni-Cr), or silver-palladium (Ag-Pd) were individually obtained, with 2 MAR conditions: disabled, and enabled. In an axial recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…Artifacts were assessed using SD of gray values and CNR in six ROIs with different distances (10 to 35 mm) and angulations (70 to 135) from the implants. The authors concluded that both modes of using MAR reduce the amount of artifacts in CBCT images, especially when the impact of artifacts in the images is more significant [23]. This finding is not completely in line with our findings.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Artifacts were assessed using SD of gray values and CNR in six ROIs with different distances (10 to 35 mm) and angulations (70 to 135) from the implants. The authors concluded that both modes of using MAR reduce the amount of artifacts in CBCT images, especially when the impact of artifacts in the images is more significant [23]. This finding is not completely in line with our findings.…”
Section: Discussioncontrasting
confidence: 57%
“…In 2022, Gomes et al investigated the effect of the artifact reduction algorithm in teeth restored with different posts and found that in the case of nickel-chromium and chromecobalt posts, these algorithms did not significantly reduce the amount of artifacts. However, in the case of silver-palladium posts, the effect of the MAR algorithm was significant [23]. This indicates that the material and alloy of the restoration were a significant factor in the effectiveness of MAR algorithms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous objective analyses have concluded that hypodense and hyperdense streaks are smoothed when MAR is enabled. 22 23 However, this homogenization of gray values in areas affected by beam-hardening artifacts does not necessarily impact diagnostic tasks. Some studies have shown that activating MAR did not enhance the detection of dehiscence and fenestration defects, nor did it aid in identifying fractured endodontic instruments.…”
Section: Discussionmentioning
confidence: 99%